Guardian of lies - Martini, Steve, 1946- (William Morrow, 2009)
"Defense attorney Paul Madriani gets caught in a web of deceit and murder involving Cold War secrets, a rare coin dealer who once worked for the CIA, and a furious assassin in one of the most entertaining novels yet in this New York Times bestselling series. A woman pauses in the hallway of a darkened San Diego beach house at night--listening for just the right moment when she can flee before her companion notices that she's gone. A man outside watches the same mansion, waiting for a sign that he can enter on his mission of blood and carnage. So begins this riveting new tale about Paul Madriani and his latest case--that of Katia, a woman accused of an unlikely crime--a trial that will unravel a careful but horrifying conspiracy. Madriani soon realizes that he's signed onto something much more sinister than a botched heist. As he searches for the truth that will clear Katia's name, he finds himself on a path that takes him from Southern California to Costa Rica, and, ultimately, to a secret buried since Castro's rise to power. Together with his partner, Harry Hinds, Madriani must piece together the threads of a decades-old conspiracy involving priceless gold coins, an aging American spy, a disaffected Russian soldier, and a forgotten weapon from the days of JFK and the Cuban Missile Crisis. As the separate strands of the story come together, Madriani finds information that will ultimately lead him to the one person who holds the key to it all: a man some call 'The Guardian of Lies'" -- from publisher's web site.